Foreign Bodies in the Ear, Nose and Throat: An Experience in a Tertiary Care Hospital in Central Nepal - Parajuli, Ramesh (International Archives of Otorhinolaryngology, 2015)
Introduction A foreign body (FB) is an object or substance foreign to the location where it is found. FBs in the ear, nose, and throat are a common problem frequently encountered in both children and adults.Objective To analyze FBs in terms of type, site, age, and gender distribution and method of removal.Methods A retrospective study was performed in a tertiary care hospital in the central part of Nepal. The study period was from June 2013 to May 2014. The information was obtained from hospital record books.Results A total of 134 patients had FBs in the ear, nose, or throat; 94 were males and 40 were females. Of the 134 patients, 70 (52.23%) had FB in the ear, 28 (20.89%) in the nose, and 36 (26.86%) in the throat. The FB was animate (living) in 28 (40%) patients with FB in the ear and 1 (3.5%) patient with FB in the nose, but the FB was inanimate (nonliving) in any patient with FB in the throat, in 42 (60%) patients with FB in the ear FB, and in 27 (96.4%) patients with FB of the nose. The FB was removed with or without local anaesthesia (LA) in 98 (73.13%) patients, and only 36 patients (26.86%) required general anaesthesia (GA). The most common age group affected was <10 years.Conclusion FBs in the ear and nose were found more frequently in children, and the throat was the most common site of FB in adults and elderly people. Most of the FBs can be easily removed in emergency room or outpatient department.
Keywords: foreign body; ear; nose; throat; endoscopy